Immunosuppression of Syrian golden hamsters accelerates relapse but not the emergence of resistance in Leishmania infantum following recurrent miltefosine pressure. (April 2019) - Hendrickx, S.; Bulté, D.; Van den Kerkhof, M.; Cos, P.; Delputte, P.; Maes, L.; Caljon, G.
Abstract: Although miltefosine (MIL) has only been approved for the treatment of visceral leishmaniasis (VL) in 2002, its application in monotherapy already led to the development of two confirmed MIL-resistant isolates by 2009. Although liposomal amphotericin B is recommended as first-line treatment in Europe, MIL is still occasionally used in HIV co-infected patients. Since their immune system is incapable of controlling the infection, high parasite burdens and post-treatment relapses are common. Linked to the particular pharmacokinetic profile of MIL, successive treatment of recurrent relapses could in principle facilitate the emergence of drug resistance. This study evaluated the effect of immunosuppression (cyclophosphamide 150 mg/kg once weekly) on the development of MIL-resistance in Syrian golden hamsters infected with Leishmania infantum . The hamsters were treated with MIL (20 mg/kg orally for 5 days) whenever clinical signs of infection or relapse were observed. The immunosuppression resulted in a significant depletion of CD4 + lymphocytes and MHCII-expressing cells in peripheral blood, and a concomitant increase in tissue parasite burdens and shorter time to relapse, but the strain's susceptibility upon repeated MIL exposure remained unaltered. This study demonstrates that immunosuppression accelerates the occurrence of relapse without expediting MIL resistance development. Graphical abstract: Image 1 Highlights: Successive treatment cycles of L. infantum in the Syrian golden hamster model do not result in MIL resistance. Immunosuppression of infected hamsters with cyclophosphamide (CPA) does not expedite the emergence of MIL resistance. Weekly CPA administration decreases the time-to-relapse and increases parasite burdens in liver, spleen and bone marrow. Immunosuppression with CPA results in a depletion of CD4 + lymphocytes and MHCII-expressing cells in peripheral blood.